Bibliometric Analysis of Statistics Journals Indexed in Web of Science Under Emerging Source Citation Index. (January 2021) - Butt, Nadeem Shafique; Malik, Ahmad Azam; Shahbaz, Muhammad Qaiser
Over the last few decades, statistics and probability became an integral part of major research areas with continuously increasing demand. This article aimed for bibliometric analysis of journals indexed in the category of "Statistics and Probability" under Emerging Source Citation Index (ESCI) of Web of Science (WoS) (2015–2019). After data extraction from WoS, the bibliometric analysis at source, author, and document levels was performed using "Bibliometrix" R-package. Out of 38 journals indexed in ESCI, 32 that fulfilled the criteria were selected. In total, 4, 294 documents were retrieved and analyzed by various bibliometric metrices, and appropriate data presentation tools were planned. Sixteen countries were found as origin of sources, mainly from USA and India while 10 countries had one journal each. Among journals, Korean Journal of Applied Statistics, Journal of Statistics & Management Systems and Advances and Applications in Statistics contributed the most. Wiley Interdisciplinary Reviews-Computational Statistics, Journal of Statistics & Management Systems, and Pakistan Journal of Statistics and Operation Research showed leading impact indices. Total number of authors were 6, 374. Only one document was cited more than 100 times. Countries collaboration network showed three main groups with minor overlap. Two clusters of keywords namely survey sampling and distribution theory were found. Overall, a consistent publication production trend was observed. Countries with relatively higher impact journals were USA, India, and Pakistan. Total citations and average citations showed dominance of developed countries. Study findings can benefit researchers and other stakeholders of the study subject to plan with better informed decisions.